IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DAN RAHMATAN LIL ALAMIN (P5RA) PADA MADRASAH IBTIDAIYAH DI KABUPATEN BONE - Herpiana, Andi; Halidin, Ali; M., Mujahidin; A., Chairullah (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This study is a field research aimed at describing the implementation of the Pancasila Student Profile Strengthening Project with the concept of Rahmatan lil ‘Alamin (P5RA) at the Madrasah Ibtidaiyah level in Bone Regency. The research employs a qualitative descriptive method, utilizing interviews, observations, and documentation for data collection. The subjects of the study include five institutions: MIN 2 Bone, MIN 7 Bone, MIN 8 Bone, MI Pondok Pesantren Modern Bone Macope, and MI Syamsu Rasyidi. The findings reveal that: (1) The implementation of P5RA is guided by the Decree of the Minister of Religious Affairs (KMA) Number 450 of 2024, which serves as a framework for curriculum implementation at Raudhatul Athfal, Madrasah Ibtidaiyah, Madrasah Tsanawiyah, Madrasah Aliyah, and Madrasah Aliyah Kejuruan. (2) The stages of P5RA implementation in the observed madrasahs include the formation of a project facilitator team, identification of school readiness, planning of dimensions, themes, and time allocation, module development, and reporting and assessment. Theme selection is based on the specific needs of each institution, with a focus on